Dampak Teknologi Informasi Terhadap Pendidikan Karakter Di Indonesia - Riris setiawati; Dhinda anggita prasmewari; Taufik Muhtarom (Journal Innovation In Education, 2024)
This study aims to determine the impact of information technology on character education in Indonesia. As well as knowing the ethical values of students in Indonesia and also knowing how the government improves the values of character education caused by current information technology. The method used in this research is descriptive qualitative method. The development of technology in modern times is increasingly rapid and we cannot avoid it, the development of technology today not only has a positive impact on people's lives, but also has a negative impact, one of which is in character education, the importance of the role of parents and teachers in character education. From the results of the study it was found that there are students now who are still very lacking in having character education caused by technology.